2003
DOI: 10.1046/j.1463-1318.2003.00416.x
|View full text |Cite
|
Sign up to set email alerts
|

Rectal endosonography can distinguish benign rectal lesions from invasive early rectal cancers

Abstract: Endorectal ultrasound can distinguish between noninvasive lesions and invasive rectal cancers clinically of stage pT0 or pT1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 24 publications
0
24
0
1
Order By: Relevance
“…In a review of cross-sectional studies investigating tumor depth in 873 patients, the overall accuracy was 85%, with sensitivity ranging from 84% in T1 to 76% in T4 [23] . Overstaging of tumor depth frequently occurs as a result of perineoplastic inflammation as ultrasound can not clearly differentiate between inflammatory and neoplastic tissue [11,24] . Similarly, preoperative biopsy causes hemorrhage and obliteration of sonographic layers [11] .…”
Section: B Amentioning
confidence: 99%
“…In a review of cross-sectional studies investigating tumor depth in 873 patients, the overall accuracy was 85%, with sensitivity ranging from 84% in T1 to 76% in T4 [23] . Overstaging of tumor depth frequently occurs as a result of perineoplastic inflammation as ultrasound can not clearly differentiate between inflammatory and neoplastic tissue [11,24] . Similarly, preoperative biopsy causes hemorrhage and obliteration of sonographic layers [11] .…”
Section: B Amentioning
confidence: 99%
“…The depth of invasion was correctly assessed in 87% (46/53) of pT1 tumors. Stark et al (59) reported their experience with high multifrequency probes. The sensitivity of ERUS with regard to invasion was 89% (16/18), specificity 88% (37/42), and accuracy 88% (53/60).…”
Section: Discussionmentioning
confidence: 99%
“…In the three multicentre studies mentioned above the diagnostic accuracy for T1 cancer was 51Á59%. However, Doornebosch [37] reported 73% and Starck [41] reported 88% accuracy for T1 cancer in single centre studies. EUS has low accuracy in patients who have had neoadjuvant chemoradiotherapy [42].…”
Section: Endorectal Ultrasoundmentioning
confidence: 99%